1986
DOI: 10.20506/rst.5.2.236
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of foot and mouth disease virus

Abstract: Work on the genetics of foot-and-mouth disease virus is reviewed, with particular emphasis on mutation and recombination as possible mechanisms of change in the virus and on the use of genetics to analyse the functions of the genome. The mutation rate has been shown to be similar to that of other RNA viruses and the regions of the genome in which mutation is tolerated are described. Work has begun on studying the accumulation of mutations under field conditions; the fac tors affecting this are clearly complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As the recombination zones analysed [14,21,29] are of different size, new programs were written to sum directly all secondary structure scores above a Total secondary structure scores per interval were obtained by adding together all percentage matches above 62 percent occurring in the zones of length indicated by nucleotide interval along the diagonal, and of 50 nucleotides width to each side. In Column 5 the ratios of total secondary structure score over number of nucleotides are given.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…As the recombination zones analysed [14,21,29] are of different size, new programs were written to sum directly all secondary structure scores above a Total secondary structure scores per interval were obtained by adding together all percentage matches above 62 percent occurring in the zones of length indicated by nucleotide interval along the diagonal, and of 50 nucleotides width to each side. In Column 5 the ratios of total secondary structure score over number of nucleotides are given.…”
Section: Figmentioning
confidence: 99%
“…In general it was found that the mean value of potential secondary structure is significantly higher in crossover zones than in recombination-free zones. Recombination increased much more steeply with increasing secondary structure in the part of the genome coding for non-structural proteins than in the 5' third of the genome coding for structural proteins.Homologous recombination in viruses with non-segmented RNA genomes was recognized in early studies using genetic markers [9,18,25], and a considerable amount of genetic evidence for recombination of picornaviruses had accumulated [4,5,13,21] before its existence was confirmed biochemically by protein and oligonucleotide separation techniques [14,28,29,31] and more recently by genome sequence data [15,27,32]. As well as in picornaviruses, recombination has recently been found to occur in coronaviruses [10,19] and in the genome of a multipartite plant virus [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation